Brain Structural Changes During Juvenile Fibromyalgia: Relationships With Pain, Fatigue, and Functional Disability. Issue 7 (19th May 2022) - Suñol, Maria; Payne, Michael F.; Tong, Han; Maloney, Thomas C.; Ting, Tracy V.; Kashikar‐Zuck, Susmita; Coghill, Robert C.; López‐Solà, Marina
Abstract : Objective: Juvenile fibromyalgia (FM) is a prevalent chronic pain condition affecting children and adolescents worldwide during a critical period of brain development. To date, no published studies have addressed the pathophysiology of juvenile FM. This study was undertaken to characterize gray matter volume (GMV) alterations in juvenile FM patients for the first time, and to investigate their functional and clinical relevance. Methods: Thirty‐four female adolescents with juvenile FM and 38 healthy adolescents underwent a structural magnetic resonance imaging examination and completed questionnaires assessing core juvenile FM symptoms. Using voxel‐based morphometry, we assessed between‐group GMV differences and associations between GMV and functional disability, fatigue, and pain interference in juvenile FM. We also studied whether validated brain patterns predicting pain, cognitive control, or negative emotion were amplified/attenuated in juvenile FM patients and whether structural alterations reported in adult FM were replicated in adolescents with juvenile FM. Results: Compared to controls, juvenile FM patients showed GMV reductions in the anterior midcingulate cortex (aMCC) region (family‐wise error corrected P [ P FWE‐corr ] = 0.04; estimated with threshold‐free cluster enhancement [TFCE]; n = 72) associated with pain. Within the juvenile FM group, patients reporting higher functional disability had larger GMV in inferior frontal regions ( P FWE‐corr  = 0.006; TFCE estimated; n = 34) linked to affective, self‐referential, and language‐related processes. Last, GMV reductions in juvenile FM showed partial overlap with findings in adult FM, specifically for the anterior/posterior cingulate cortices ( P  = 0.02 and P  = 0.03, respectively; n = 72). Conclusion: Pain‐related aMCC reductions may be a structural hallmark of juvenile FM, whereas alterations in regions involved in emotional, self‐referential, and language‐related processes may predict disease impact on patients' well‐being. The partial overlap between juvenile and adult FM findings strengthens the importance of early symptom identification and intervention to prevent the transition to adult forms of the disease.